Variabilidade genética em populações naturais de Ziziphus joazeiro Mart., por meio de marcadores moleculares RAPD - Gois, Itamara Bomfim (2014)
The studies of genetic diversity in natural populations are essential to the elaboration of conservation strategies. Thus, this work was carried out to genetically characterize natural populations of Ziziphus joazeiro Mart., by RAPD (Random Amplified Polymorphic DNA) markers, located in the region of Baixo São Francisco, Sergipe. 20 primers were used and, from the observed polymorphism, the genetic similarity ( ), the characterization of genetic variability and the percentage of polymorphism were estimated by Jaccard’s coefficient. The Mantel test was performed to evaluate the correlation between the genetic similarity and the geographic distance and the gene flow was also estimated. The observed polymorphism in the Z. joazeiro populations ranged from 58.1 to 66.5% and the genetic similarity from 44 to 54%. The genetic similarity observed is not correlated with the geographic distance. The values observed to the Nei’s genetic diversity, to the Shannon’s index, and to the parameters HS, HT and GST were considered high and similar to those found in other forest species. The percentage of polymorphic loci was considered low. The highest genetic identity was observed between the populations of Canindé do São Francisco, and Santana do São Francisco and the highest genetic distance between the populations of Canhoba and Canindé do São Francisco. The gene flow was higher than 1. Based on the results it can be stated that there is high genetic variability between the populations, and genetic structuring may be occurring.